2015
DOI: 10.5901/mjss.2015.v6n3p781
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Model of Making a Decision in the Conditions of Uncertainty (Correlation Of Interests and Preferences in Regional Systems)

Abstract: The solution of the problem of environmental management is connected with the capabilities of mathematical-geographic modelling on the basis of modern conceptual ideas the characteristic feature of which is the interpretation of environment as an entity determined by the dialectic unity of its natural and socio-economic components. It's important to admit that not allrelations in geography may be presented at a strict formal level, which determines wide opportunities for evaluation of interaction in environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In the course of the study it was found out that for these Copyright © 2018 Helix ISSN 2319 -5592 (Online) regions there is a significant isolation of many settlements from the regional center. For these areas, the transport problem remains extremely important [14,15]. Therefore, it is necessary to solve the problem of isolation of rural settlements, ensuring their interrelation with each other, and with district centers.…”
Section: Discussionmentioning
confidence: 99%
“…In the course of the study it was found out that for these Copyright © 2018 Helix ISSN 2319 -5592 (Online) regions there is a significant isolation of many settlements from the regional center. For these areas, the transport problem remains extremely important [14,15]. Therefore, it is necessary to solve the problem of isolation of rural settlements, ensuring their interrelation with each other, and with district centers.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the inflow of population to the region increases the demand and supply of goods, the formation of the tax base, economic growth and development of the region as a whole. Otherwise, the outflow of population from the concrete territory indicates either bad living conditions or low quality of life [8].…”
Section: Introductionmentioning
confidence: 99%